(untitled) (GEOMATE Journal, 2024)
Concrete is the most widely used construction material, but its production consumes a large amount of natural resources and generates significant carbon emissions. In recent years, there has been growing interest in using waste materials and recycled products in concrete production to reduce its environmental impact. This study investigates the use of polystyrene plastic as a replacement for gravel in concrete production, particularly for structural applications. A mixed design methodology was employed to prepare three different concrete mixtures: conventional concrete, polystyrene concrete, and coated polystyrene concrete. The main findings of this study indicate that the full replacement of gravel with polystyrene plastic achieved the minimum compressive strength required for structural use. The study also demonstrated that using polystyrene plastic in concrete can reduce its overall weight and improve workability. The significance of this research lies in its potential to reduce the environmental impact of concrete production by incorporating recycled plastic waste as a substitute for natural resources. This study provides valuable insights into the use of polystyrene plastic in concrete, which could inform the development of more sustainable construction practices in the future.